Forest-clearing to create early-successional habitats: Questionable benefits, significant costs - Kellett, Michael J.; Maloof, Joan E.; Masino, Susan A.; Frelich, Lee E.; Faison, Edward K.; Brosi, Sunshine L.; Foster, David R. (Frontiers in Forests and Global Change, 2023)
A campaign is underway to clear established forests and expand early-successional habitats — also called young forest, pre-forest, early seral, or open habitats — with the intention of benefitting specific species. Coordinated by federal and state wildlife agencies, and funded with public money, public land managers work closely with hunting and forestry interests, conservation organizations, land trusts, and private landowners toward this goal. While forest-clearing has become a major focus in the Northeast and Upper Great Lakes regions of the U.S., far less attention is given to protecting and recovering old-forest ecosystems, the dominant land cover in these regions before European settlement. Herein we provide a discussion of early-successional habitat programs and policies in terms of their origins, in the context of historical baselines, with respect to species’ ranges and abundance, and as they relate to carbon accumulation and ecosystem integrity. Taken together, and in the face of urgent global crises in climate, biodiversity, and human health, we conclude that public land forest and wildlife management programs must be reevaluated to balance the prioritization and funding of early-successional habitat with strong and lasting protection for old-growth and mature forests, and, going forward, must ensure far more robust, unbiased, and ongoing monitoring and evaluation.